The impact of interlocking directorates on corporate performance of Bursa Malaysia listed companies - Saidin, Norhaniza; Malik @ Malek, Mazrah; Saidin, Saidatunur Fauzi (Universiti Putra Malaysia Press, 2013)
One of the main concerns about interlocking directorates is their effect on corporate performance; however, there is little research undertaken on this issue. Therefore, the objective of this study is to examine the effect of interlocking directorates on corporate performance by considering the nature and the direction of interlocking. The analyses are based on the data of 741 listed companies on Bursa Malaysia in 2007. The Ordinary Least Square regression results show that the number of interlocking companies, inter-industry interlocking directorates and interlocking created by independent directors are all significant and positively related to corporate performance, which is consistent with the resource dependence theory and the corporate governance theory. However, it is also discovered that both multiple directorships by executive directors and non-executive non-independent directors do not have any effect on corporate performance, which is consistent with the class integration theory. Despite the negative perception on interlocking directorates by the public, the findings suggest that interlocking directorates actually benefit shareholders by enhancing the earnings performance of the corporation.